The Israeli-Palestinian conflict a people's war - Milton-Edwards, Beverley (Routledge, 2009)
Framing the debate and analysis around issues such as Zionism, Palestinian nationalism, international peace efforts, the refugees, state-building, democracy and religious opposition and highlighted by first hand quotes and sources of the conflict from its major participants, Beverley Milton-Edwards explores the deep impact of the conflict on regional politics in the Middle East and why the enmity between Palestinians and Israelis has become a number one global issue drawing in the world's most important global actors.